2017
DOI: 10.25167/ees.2017.44.11
|View full text |Cite
|
Sign up to set email alerts
|

Ergonomics Awareness and Employee Performance: An Exploratory Study

Abstract: Abstract:The study examined the effects of ergonomics on employee performance by ascertaining the level of ergonomics awareness in Nigerian organizations, identifying the factors hindering the use of ergonomic, and the best practices and methods adopted by various organizations across industries. Despite a knowledge of importance to a growing number of researchers in Nigeria, there is still a dearth in knowledge of ergonomics design and its implementation in Nigeria. This can be observed in the low level of it… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 8 publications
0
10
0
Order By: Relevance
“…For example, the present finding on non-provision of ergonomics comfortable computer workstation is in consonance with the findings of Asaolu and Itsekor (2014), (Momodu Bayo et al, 2014), (Jomoah, 2014) who found that the incidences of general complaints of computer users surround the poor or decrease in work station ergonomics provisions. In Nigeria, this can be in connection with recent findings by Olabode et al (2017) that several factors such as awareness, resources constraints, communication and integration disconnection between employees and equipment designers, technological changes and insufficient relevant studies inhibited the efficient implementations in Nigeria. On the other hand, in respect of the effect of age on computer induced distress, the present finding is in contrary to some recent finding by Jena and Mahanti (2014), and Mahalakshmi and AllySornam (2013) who reported significant effect of age on technostress.…”
Section: Discussionmentioning
confidence: 57%
See 1 more Smart Citation
“…For example, the present finding on non-provision of ergonomics comfortable computer workstation is in consonance with the findings of Asaolu and Itsekor (2014), (Momodu Bayo et al, 2014), (Jomoah, 2014) who found that the incidences of general complaints of computer users surround the poor or decrease in work station ergonomics provisions. In Nigeria, this can be in connection with recent findings by Olabode et al (2017) that several factors such as awareness, resources constraints, communication and integration disconnection between employees and equipment designers, technological changes and insufficient relevant studies inhibited the efficient implementations in Nigeria. On the other hand, in respect of the effect of age on computer induced distress, the present finding is in contrary to some recent finding by Jena and Mahanti (2014), and Mahalakshmi and AllySornam (2013) who reported significant effect of age on technostress.…”
Section: Discussionmentioning
confidence: 57%
“…In spite of this observation by past empirical studies, it is still a concern to researchers (Ismaila, 2010;Oladeinde, Ekejindu, Omoregie, & Aguh, 2015) in the growing field of ergonomic on the 49│ Development and validation of computer induced distress and factors influencing technostress among ICT users increase in work-related health problem among the ICT users especially in developing nations. Some studies in Nigeria (Funminiyi et al, 2014;Momodu Bayo et al, 2014;Olabode, Adesanya, & Bakare, 2017) have identified that the positioning and posture of computer users resulted in musculoskeletal disorders due to poor workstations design or inappropriate work environment. For instance , Johnson, Onigbinde, Onasanya, Emechete, and Gbela (2009) observed in Nigeria University community, that common complaint among computer users is back pain, neck, eyes and wrist pain.…”
Section: Introductionmentioning
confidence: 99%
“…Not only in Brazil, but the prevalence of occupational illness is also increasing steeply in many developing countries where the knowledge and significance of ergonomics are meagre. This finding was endorsed by [22] Olabode et al (2017) in a study which indicated the absence of strict legislation and reforms as the reason for this. Such an indication suggests the need for potential intervention in industries based on the nature of occupational hazards [23].…”
Section: Introductionmentioning
confidence: 80%
“…Other research has shown that even with great knowledge of ergonomics, employees often do not use their knowledge in practice (Modi, Kuswaha, Dave, 2013;Sirajudeen, Pillai, Vali, 2013). Authors dealing with these issues have noticed that companies lack the promotion of responsibility, awareness and safe behaviour among employees (Kamińska, Tokarski, 2012;Olabode, Adesanya, 2017;Paul, 2012;Romankow, 2015).…”
Section: Introductionmentioning
confidence: 99%